Build Trust Consumer in Sharia E-Commerce Ecosystem : A Study Exploring the Young Indonesian Muslim Market - Mohamad Maulana Ridzki; Satrio Rafli Firmansah (Journal of Strategic Marketing and Applied Economics, 2025)
Digital transformation has push growth rapid growth of e-commerce in Indonesia, including the emergence of a platform that carries principles sharia . In the middle trend global halal consumption and the increase awareness religious among​ generation young Muslims, beliefs become element crucial in determine sustainability e-commerce ecosystem based sharia . However , not yet Lots studies that examine factor former trust in context this , especially in the young Indonesian Muslim market which has preference unique and sensitive to values ethics . Research This aim For explore in a way deep factors that influence formation trust young Muslim consumers towards sharia e-commerce . Approach qualitative used with method studies exploratory through interview deep to 15 informants active 18–30 year olds​ Shopping on Sharia e-commerce platforms . Research results show that trust formed by four factor main : commitment to principle sharia , transparency information , integrity perpetrator business , and consistent digital experience . In addition that , halal certification , zakat/ infak features , and narrative religious become Power pull emotional strengthening​ loyalty . Research This give contribution to development theory trust in context marketing based mark as well as become reference for sharia e-commerce platform developer in design more marketing strategies​ adaptive to characteristics young Muslim consumers.